THE CHSE (Cleanliness, Health, Safety, and Environment) Program for New Normal Life in Tijili Benoa Curated Artotel - Ita Supeno; I Gede Mudana; Ni Gst Nym Suci Murni (Catuspata Press, 2021)
Abstract : Purpose: This research aims to analyze the CHSE (cleanliness, health, safety, and environment) program in a hotel so that the level of the hotel room occupancy can be increased especially due to Covid-19 pandemic. Research methods: This is a qualitative research. The data collection method is literature study which is obtained from the Human Resources Department of Tijili Benoa Curated Artotel, Bali, Indonesia. Findings: Tijili Benoa Curated Artotel is still using WHO guidelines where the CHSE program is not fully complete according to the regulations of the Ministry of Tourism and Creative Economy. Currently what has been done by Tijili Benoa Curated Artotel is the guidelines taken from the WHO decision. Implications: The program can be developed in accordance with the latest Kemenparekraf (Kementerian Pariwisata dan Ekonomi Kreatif) guidelines so that the hotel can be certified CHSE and can develop future strategies in increasing room occupancy.